Desejos e vontades da pessoa idosa institucionalizada na terminalidade da vida - Possatti, Fabiane Marzari (2023)
The wishes and wishes of elderly people residing in long-term care facilities at the end of life must be identified and described, as the preservation of decision-making capacity must be respected. The objective is to know the desires and wishes of elderly people residing in Long Stay Institutions for the Elderly in the terminality of life. This is a qualitative, descriptive and exploratory research in which 18 elderly people from two Long Stay Institutions for the Elderly in a city in the center of the state of Rio Grande do Sul participated. Data collection took place from March to May 2022, through semi-structured interviews and using the resource of cards on the table. The data were submitted to discursive textual analysis. Approval was obtained from the Ethics and Research Committee with human beings, according to opinion number 5219665. Five categories emerged: embracement and acceptance by the family: death in the ILPI or at home and the fear of dying alone; end of a life cycle: moment of personal rescue, farewell, affection and faith; preservation of the human dignity of the elderly who are institutionalized at the end of life; not being pressured and not being a burden for the family: desires related to the action of professionals and family members with the elderly person and maintenance of the senses and awareness of death: desire for a beneficial experience, without pain, purification and delivery through faith. The elderly person considers important the acceptance of their death by their family members, given the terminality of life, combined with the presence of spirituality and divine protection that provide them with the conviction that they will not be alone. They want to rescue affection, forgiveness, gratitude for the family and faith in the end of life. He asserted himself about the preservation of human dignity, the financial organization as a promoter of the achievement of autonomy, and the desire not to be pressured and a burden for the family. They expressed the desire to be cared for by family members, maintain their autonomy, awareness of the end of life and adequate analgesia so that death is a beneficial experience. Finally, desires and wishes are related to the way they would like to be cared for by health professionals, but primarily because they want broad aspects of life. Residents are generally willing to talk about their wants and desires, and that end-of-life preferences are diverse, individual, and malleable. This research will collaborate so that the actions of health professionals are based on the wills and desires of institutionalized elderly people, so that they safeguard their dignity in the terminality of life.